Tratamento da leucoplasia bucal com criocirurgia associada ou não ao laser de baixa intensidade: um estudo preliminar. - Adriana Spindola Ribeiro (2009)
Cryosurgery is a therapeutic method characterized by safe, simple application, and effectiveness. It is used in the treatment of oral leukoplakia (OL), the most common premalignant lesion of oral cavity. One of the principal side effects associated to surgical treatment of the OL is post-operative pain. The low level laser therapy (LLLT) has been used to decrease the pain in various conditions. The objective of this study was to investigate the effect of cryosurgery in clinical resolution of OL and its association or not with LLLT on pain relief. Eighteen patients with OL were divided randomly in two groups: ten treated with cryosurgery only (Group 1) and eight treated with cryosurgery associated of the LLLT (Group 2). Cryosurgery was performed with Cry-Ac® apparatus. The LLLT was performed three times in the week and a numerical rating scale was used to measured pain. The treatment was well-tolerated, treated OL sites appeared clinically normal and without clinical evidence of recurrence until the present time. It was also observed a tendency of group 2 to have less pain than group 1. Our results demonstrate that OL may be treated by cryosurgery and the association with LLLT contributes to minimize the post-operatory pain.